Exploring the World of Late Talkers: Unraveling Language Learning Behaviors - Barrera, Sheilby Jill C; Balones, Jerlyn (Journal of Social Work and Science Education, 2022)
This research aimed to determine the learning behaviors of the children with late language emergence. This study specifically sought to determine the parents’ experience when facilitating their language learning intervention to their children. Thus, it aims to identify the struggles and rewarding instances of the participants as they teach their child to grow with language. The researcher used a qualitative approach to uncover the trends in thoughts and opinions and to dive deeper into the problem. The participants were chosen personally by the researcher and all of them is encountering the same problem being their child is a late talker. The findings of this study showed that the participants observed that their children has a common behavioral patterns and behavioral learnings. This shows that late talkers has the same manner of keeping up with the pace and has and identical way of learning when it comes to language acquisition. This paper evaluated the struggles, experiences, and rewarding instances of parents when facilitating the learning of their late talker children.